ChemInform Abstract: Aptasensors for Small Molecule Detection. Issue 3 (22nd January 2013) - Walter, Johanna‐Gabriela; Heilkenbrinker, Alexandra; Austerjost, Jonas; Timur, Suna; Stahl, Frank; Scheper, Thomas
Abstract Review: 70 refs.